Screening of inmates transferred to Spain reveals a Peruvian prison as a reservoir of persistent Mycobacterium tuberculosis MDR strains and mixed infections - Abascal E. (2020)
It is relevant to evaluate MDR-tuberculosis in prisons and its impact on the global epidemiology of this disease. However, systematic molecular epidemiology programs in prisons are lacking. A health-screening program performed on arrival for inmates transferred from Peruvian prisons to Spain led to the diagnosis of five MDR-TB cases from one of the biggest prisons in Latin America. They grouped into two MIRU-VNTR–clusters (Callao-1 and Callao-2), suggesting a reservoir of two prevalent MDR strains. A high-rate of overexposure was deduced because one of the five cases was coinfected by a pansusceptible strain. Callao-1 strain was also identified in 2018 in a community case in Spain who had been in the same Peruvian prison in 2002–5. A strain-specific-PCR tailored from WGS data was implemented in Peru, allowing the confirmation that these strains were currently responsible for the majority of the MDR cases in that prison, including a new mixed infection. © 2020, The Author(s).